Hydraulic power take off system for wave energy utilization. Issue 1 (January 2021) - Velichkova, R; Pushkarov, M; Angelova, R A; Simova, I; Markov, D; Denev, I; Stankov, P
Abstract: Wave energy from seas and oceans is among the most promising and abundant energy sources on the Earth. There are different designs of conversion systems for the utilization of the wave energy, resulting from the different ways of the wave energy absorption, and depending on the location characteristics. The paper proposes a new hydraulic power take-off system (PTOS) that can be used in various types of wave energy conversion systems.